Optimization of Threads Production on Thin - Walled Castings - Stančeková, Dana; Mrázik, Jozef; Rudawska, Anna; Ťavodová, Miroslava; Miturska-Barańska, Izabela; Sršníková, Daniela; Špiriak, Miroslav (Manufacturing Technology Journal, 2023)
This study focuses on the analysis and solution of thread production in thin-walled profiles. It explores three different threading technologies, including cutting, forming, and extrusion. The issue of a screw joint in a thin-walled component is complex due to the stiffness of the joint and the short length of the thread. Hence, the careful choice of a suitable manufacturing process for producing inner threads in thin-walled components holds significant importance. The study entails monitoring the hardening of surface layers of materials after thread production, in conjunction with the acquisition of microstructure images of the experimental material. The outcome is a comparative evaluation of different individual thread production technologies.
Keywords: Thread cutting; Thread forming; Thread pressing; Thin-walled profile